Salmonella and Campylobacter spp. in Northern Elephant Seals, California - Stoddard, Robyn A.; Gulland, Frances M.D.; Atwill, E. Rob; Lawrence, Judy; Jang, Spencer; Conrad, Patricia A.
Campylobacter and Salmonella spp. prevalence and antimicrobial drug sensitivity were determined in northern elephant seals that had not entered the water and seals that were stranded on the California coast. Stranded seals had a higher prevalence of pathogenic bacteria, possibly from terrestrial sources, which were more likely to be resistant.